Effect of Acid-Base Composition on Physical Characteristicsand Antioxidant Activity of “Beras Kencur” EffervescentTablet - Astuti, Widi; Putri, Radenrara Dewi Artanti; Sulistyaningsih, Triastuti; Azany, Ghaefira Tasya; Alexandra, Natasya Viona; Saputri, Ria; Jannah, Reni Ainun; Hadikawuryan, Danang Subarkah; Fitri, Zulfa Ajrina (Sainteknol : Jurnal Sains dan Teknologi, 2024)
This study aimed to evaluate the effect of acid-base ratio on the physical characteristics and antioxidant activity of the beras kencur effervescent tablet formulation. The formulation determination was based on the percentage inhibition value, where the highest value (76.2%) was found in beras kencur at 10 mg/mL, so that 1.5 g is needed to achieve the highest potential of radical scavenging activity. In this case, 1.5 g of sample was then incorporated into three effervescent tablets. The acid-to-base ratios used in this study were 1: 1.25 (F1), 1: 1.50 (F2), and 1: 2.50 (F3). The tablets were evaluated for pH, dissolution time, total phenolic content (TPC), and antioxidant activity. The results showed that a higher proportion of base (F3) improved solubility. Meanwhile, antioxidant activity evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) test, and total phenolic content determined using Folin-Ciocalteau, showed that tablets with a higher proportion of acid exhibited higher total phenolic content. However, considering that all three samples have very strong antioxidant activity, it can be concluded that F3 is the optimal formulation.